2016
DOI: 10.1111/jsr.12464
|View full text |Cite
|
Sign up to set email alerts
|

Modelling maintenance of wakefulness in rats: comparing potential non‐invasive sleep‐restriction methods and their effects on sleep and attentional performance

Abstract: Summary While several methods have been used to restrict the sleep of experimental animals, it is often unclear whether these different forms of sleep restriction have comparable effects on sleep–wake architecture or functional capacity. The present study compared four models of sleep restriction, using enforced wakefulness by rotation of cylindrical home cages over 11 h in male Wistar rats. These included an electroencephalographic‐driven ‘Biofeedback’ method and three non‐invasive methods where rotation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…However, 10 h of total sleep deprivation using this novel paradigm did not prevent a significant rise of corticosterone [81]. Other methods, based on real-time EEG or EMG biofeedback systems triggering the rotation of cylindrical cages or running wheels when NREM sleep, REM sleep or inactivity are detected, were able to prevent sleep for 6-11 h in male rats and mice with a mild but non-significant increase in corticosterone [77,82].…”
Section: Do Sleep-deprivation Procedures In Rodents Affect the Level mentioning
confidence: 71%
See 1 more Smart Citation
“…However, 10 h of total sleep deprivation using this novel paradigm did not prevent a significant rise of corticosterone [81]. Other methods, based on real-time EEG or EMG biofeedback systems triggering the rotation of cylindrical cages or running wheels when NREM sleep, REM sleep or inactivity are detected, were able to prevent sleep for 6-11 h in male rats and mice with a mild but non-significant increase in corticosterone [77,82].…”
Section: Do Sleep-deprivation Procedures In Rodents Affect the Level mentioning
confidence: 71%
“…Despite this study's conclusion stating that the overall low level of stress was unlikely to substantially alter sleep patterns during recovery, the immediate but transient effects of forced locomotion on corticosterone release, and thus subsequent effects on sleep parameters and underlying sleep-regulating mechanisms, cannot be ignored. Furthermore, other studies have shown that sleep deprivation, fragmentation or restriction by forced locomotion for 11-48 h in rats markedly increased the release of corticosterone [72][73][74][75][76][77]. In mice, 24 h of sleep deprivation using an activity wheel did not cause a significant increase in corticosterone [78], while another study showed that chronic sleep interruption during 14 days using a rotating drum induced an increase in corticosterone [79].…”
Section: Do Sleep-deprivation Procedures In Rodents Affect the Level mentioning
confidence: 93%
“…The aim of the present study was to assess the effects of feeding condition (i.e. ad libitum-fed vs. food restriction) at baseline and on SR induced changes in performance of a simple response latency task (SRLT) in rats [26]. In addition, the effects of SR and food restriction on performance of a progressive ratio (PR) test were measured.…”
Section: Introductionmentioning
confidence: 99%
“…Breakpoint is considered to be an index of present state of motivation of the animal to obtain the reward. The EEG was recorded to quantify sleep and event-related potentials (ERP) during the SRLT to gain further insight into cognitive processes, and how they are affected by sleep loss and food restriction [26,28].…”
Section: Introductionmentioning
confidence: 99%
“…These dynamic changes in the EEG display various amplitudes (i.e., low amplitude in wakefulness and REM sleep and high amplitude in NREM sleep) and specific spectral features. Analysis of the EEG is based on the visual and/or automated scoring of vigilance states on epochs of various durations using defined criteria both in humans [8,9] and rodents [10,11]. Fourier Transform-based signal analysis has provided essential information about the amplitude and frequency features of the EEG associated with the different vigilance states, characterised by power density spectra revealing frequency components of the signal [12].…”
Section: Introductionmentioning
confidence: 99%